1998
DOI: 10.1161/01.str.29.1.203
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase of Manganese–Superoxide Dismutase in Remote Brain Areas After Focal Photothrombotic Cortical Lesion

Abstract: Background and Purpose-Free radicals including superoxide are responsible for postlesional cytotoxicity. In contrast to the constitutive CuZn-superoxide dismutases (SODs), manganese-superoxide dismutase (Mn-SOD) is inducible and has the potential to protect neurons by its superoxide dismutating activity. Therefore, we studied the presence and the regional changes in Mn-SOD within the brain after focal cortical ischemia. Methods-Focal cortical photothrombotic lesions were produced in the hindlimb region of rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 60 publications
6
36
0
Order By: Relevance
“…Increased immunoreactivity of manganese-superoxide dismutase and expression of damage-induced neuronal endopeptidase mRNA was observed in the ipsilateral thalamus after MCA occlusion in rats. 42,43 Superoxide dismutases are known to effectively scavenge superoxide radicals and protect neurons from oxidative damage, and damage-induced neuronal endopeptidase can be upregulated in response to neuronal insult and activate superoxide dismutases. Therefore, the elevation of manganese-superoxide dismutase and damage-induced neuronal endopeptidase may reflect increased oxidative stress in the ipsilateral thalamus.…”
Section: Oxidative Damagementioning
confidence: 99%
“…Increased immunoreactivity of manganese-superoxide dismutase and expression of damage-induced neuronal endopeptidase mRNA was observed in the ipsilateral thalamus after MCA occlusion in rats. 42,43 Superoxide dismutases are known to effectively scavenge superoxide radicals and protect neurons from oxidative damage, and damage-induced neuronal endopeptidase can be upregulated in response to neuronal insult and activate superoxide dismutases. Therefore, the elevation of manganese-superoxide dismutase and damage-induced neuronal endopeptidase may reflect increased oxidative stress in the ipsilateral thalamus.…”
Section: Oxidative Damagementioning
confidence: 99%
“…18 -21 The previous studies revealed that neurons and/or glial cells immunoreactive to Mn-SOD increased in the boundary zone of infarction in the rat striatum after 60 minutes of MCAO, 19 in the gerbil hippocampus after 2 minutes of forebrain ischemia, 20 and in remote brain areas after focal cortical ischemia. 21 On the other hand, Kondo et al 22 reported that iron accumulated in the hippocampal CA1 region, layers III-V of the parietal cortex, and frontocortical layer V in rats after 30 minutes of forebrain ischemia.…”
Section: Serial Change In the Caudoputamen Of Rats After 15-minute Mcaomentioning
confidence: 99%
“…After deparaffinization, sections were incubated overnight with primary polyclonal antibody raised to full length rat SOD2 protein (Abcam Inc., ab13534) at 1:1000 dilution. This antibody has a broad spectrum of species reactivity (Drosophila and vertebrate) and its specificity has been confirmed by western blotting at 1/2000 dilution to a single band (Saha and Pahan, 2007;Bidmon et al, 1998;Liu et al, 1993). A biotinylated secondary anti-rabbit antibody and standard ABC-peroxidase reagents (Vector Laboratories) were applied.…”
Section: Methodsmentioning
confidence: 99%